Ruang Publik sebagai Representasi Kebijakan dan Medium Komunikasi Publik - Malik, Abdul (Sawala : Jurnal Administrasi Negara, 2018)
This study aims to analyze how public space can be a representation of public pride and its contribution as a medium of public communication. The selection of Serus City public space locus research which is objectively the Capital of Banten Province is expected to be a representation and role model for cities with ideal public spaces. The method used is a qualitative approach. The technique carried out by researchers is a survey of academic literature in the field of public policy and communication in order to obtain concepts that are relevant to research. The technique of collecting data is through searching various sources and literature both from government documents and reporting on print and electronic mass media, journals and books related to public administration and communication. The results of the study indicate that the management of public spaces in Serang City still does not represent pro-public policies, this is a challenge for public policy stakeholders in Serang City in formulating the management of ideal public spaces. The objective condition of Serang Citys public space still cannot be a medium of public communication that is able to encourage freedom of thought and egalitarian action in the public sphere.